Revivalism and Decoloniality: The Paradox of Modernization without Westernization in the Political Theology of Israr Ahmad - Rehman, Mohammad Adnan (Religions, 2023)
This article explores the contribution of modern Muslim revivalism to Muslims’ political decolonization, and the paradoxical role the West plays in that process. On the one hand, revivalism rejects the founding principles of liberal political theory, and on the other hand, it readily adopts the salient structures and mechanisms of the modern polity with a view to Islamize them, all the while insisting on the Muslims’ need to de-Westernize. Toward revealing the hitherto neglected dimensions of revivalism, my analysis adopts an unconventional route by subjecting revivalism to a semiotic analysis in conversation with the archetypal theories of Mircea Eliade and Carl G. Jung. The analysis unveils the universal psychological structures of revival, and their specific Muslim symbolization. I conclude (a) that depth psychology makes modern Muslim revival inevitable, which will only grow stronger and gain wider appeal while the Muslims continue to suffer decline; (b) that among the different forms of Muslim revival, revivalism ventures the farthest in decolonizing Muslim political imagination; (c) that the revivalist imagination makes their espoused caliphate imperative for the purpose of ritual participation in Islam’s sacred origins; and (d) that a critical reconstruction and evolution of revivalism holds out the promise of a greater contribution to Muslim decolonization. For my analysis, I largely turn to the Pakistani political theologian Israr Ahmad (d. 2010), whose ideas have been disseminated widely across the Muslim world, yet who has not received the requisite academic scrutiny. Moreover, intra-revivalist critique of revivalism has been a neglected aspect in the study of revival, and its careful scrutiny should become a topic of investigation in its own right. In that regard, Ahmad offers a most important critique of earlier revival efforts and their entanglement with certain aspects of coloniality.